Cultivating effective corpus use by language learners. Issue 1 (17th February 2017) - Kennedy, Claire; Miceli, Tiziana
ABSTRACT: While there is widespread agreement on the expected benefits of hands-on access to corpora for language learners, reports abound of the difficulties involved in realising those benefits in practice. A particular focus of discussion is the challenge of transferring the skills of the corpus linguist to learners, so that they can explore this type of monolingual and unmediated resource effectively in a 'learner-as-researcher' or 'learner-as-detective' role. In this paper, we present a positive experience of an apprenticeship in corpus use, which we attribute to a training approach that seeks to exploit the unmediated nature of corpora rather than treating it as a problem for learners. Our approach is not aimed at equipping learners with skills that will allow them to derive rules from the systematic analysis of corpus data. Instead we aim to inculcate in our students a propensity for open-ended searches, and an observe-and-borrow-chunks mentality, oriented to copying models from a corpus to enrich and render more accurate their written production in particular. We also see this training process as encouraging their curiosity about language patterns and authentication of the use they make of such patterns, and therefore beneficial to their ongoing development as independent language learners more generally.